Impact Of Early Mobilization Video Education On Patient Motivation In Mothers After Cesarean Section - Nining Istighosah; Agusta Dian Ellina; Eri Puji Kumalasari; Reni Yuli Astutik; Suci Anggraeni; Herlina Yuyun Saputri (Journal of Health Science Community, 2025)
Early post-SC mobilization is very important to speed up the mother’s recovery process after a cesarean section. One way to increase mothers’ understanding and motivation in carrying out early mobilization is by providing information through videos. The aim of this research was to determine the effect of the post SC early mobilization video education method on patient motivation before and after being given education at Permata Hati Way Jepara Hospital. This research is quantitative with a one group pre-post test design. Data were collected using a questionnaire to assess the level of motivation before and after being given education using a video about early post-SC mobilization. The number of respondents was 45 respondents using total sampling technique. The data obtained was processed statistically using the Wilcoxon test. The research results show that the level of motivation of respondents before being given education using the video method was that 23 respondents (51.1%) had high motivation and 22 respondents (48.8%) had low motivation. After respondents were given education, the number of respondents who had high motivation increased, as many as 39 respondents (86.6%) had high motivation and 6 respondents (13.3%) had low motivation. The P value in the Wilcoxon test between motivation before and after being given the intervention is 0.001 (< 0.05), which means that there is an influence of education using the video method on patient motivation in carrying out early post-SC mobilization. There is an influence of the post SC early mobilization video education method on patient motivation before and after being given video education at Permata Hati Way Jepara Hospital.